2015
DOI: 10.1007/s11104-015-2512-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functional diversity and structure of phytate-hydrolysing bacterial community in Lolium perenne rhizosphere

Abstract: Background and aims Plant growth is frequently limited by the availability of inorganic phosphorus (P) in the soil. In most soils, a considerable amount of the soil P is bound to organic molecules. Of these, phytate is the most abundant identifiable organic P form, but is not readily available to plants. In contrast, microorganisms have been shown to degrade phytate with high efficiency. The current study aims to characterize the members of the phytate-hydrolysing bacterial community in rhizosphere, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
(123 reference statements)
2
9
0
Order By: Relevance
“…Likewise, our findings of Firmicutes in the Ca-IP6+RE hotspots fit with previous studies showing that the phyla, and specifically the genus Bacillus, responds quickly to additions of organic material ; (Fierer et al 2007). Finally, our Ca-IP6 hotspot findings further compliment the findings by Sanguin et al (2016) who employed a culture-independent 16S rRNA gene-DGGE study of the grass rhizosphere, and showed predominance of Proteobacteria and Actinobacteria in Na-phytate treated alkaline soils.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, our findings of Firmicutes in the Ca-IP6+RE hotspots fit with previous studies showing that the phyla, and specifically the genus Bacillus, responds quickly to additions of organic material ; (Fierer et al 2007). Finally, our Ca-IP6 hotspot findings further compliment the findings by Sanguin et al (2016) who employed a culture-independent 16S rRNA gene-DGGE study of the grass rhizosphere, and showed predominance of Proteobacteria and Actinobacteria in Na-phytate treated alkaline soils.…”
Section: Discussionsupporting
confidence: 91%
“…Third, the BPP primers employed do not cover enough sequence variability to capture the full BPP profile. Whilst there have been various attempts to develop degenerate BPP primers (Huang et al, 2009, Jorquera et al, 2013, Lim et al, 2007; a broad consensus remains however that the currently available primers are unable to capture the BPP profile believed to be present based on in-vitro evidence (Sanguin et al 2016). Finally, there is the possibility that another novel or overlooked phytase acts in alkaline-buffered systems.…”
Section: Discussionmentioning
confidence: 99%
“…Some species of bacteria, including Bacillus spp., possess the ability to mineralize and solubilize organic and inorganic phosphorus in the soil for quick access to the plant ( Barea and Richardson, 2015 ). Microbial phytases, specially produced by Bacillus spp., were studied due to their PGP effects and diverse agrobiotechnological applications ( Kumar et al., 2013 ; Sanguin et al., 2016 ). Besides solubilizing phytate phosphorous, extracellular phytases produced by Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the BPP primers employed do not cover enough sequence variability to capture the full BPP profile. While there have been various attempts to develop degenerate BPP primers (Huang et al, 2009, Jorquera et al, 2013, Lim et al, 2007; a broad consensus remains that the currently-available primers are unable to capture the BPP profile believed to be present based on in-vitro evidence (Sanguin et al, 2016). Finally, there is the possibility that another novel or overlooked phytase acts in alkaline-buffered systems.…”
Section: Quantified 16s Rrna and Phosphatase Gene Abundancementioning
confidence: 99%